Improvement of bioethanol production in Consolidated Bioprocessing (CBP) via consortium of Aspergillus niger B2484 and Trichoderma asperellum B1581 - Mohamed Ghazali, Mona Fatin Syazwanee; Mustafa, Muskhazli; Mohd Zainudin, Nur Ain Izzati; Abd Aziz, Nor Azwady (Universiti Putra Malaysia Press, 2021)
Consolidated bioprocessing (CBP) in bioethanol production involves the combination of four essential biological procedures in a single bioreactor, using a mixture of organisms with favourable cellulolytic ability without the addition of exogenous enzymes. However, the main disadvantage of this process is the complexity to optimise all factors considering both enzymes and microbial activity at the same time. Hence, this study aimed to optimise suitable culture conditions for both organisms to work efficiently. Six single factors that are considered crucial for bioethanol production were tested in one-factor-at-a-time (OFAT) analysis and analysed using Response Surface Methodology (RSM) software for Aspergillus niger B2484 and Trichoderma asperellum B1581 strains. The formulation of a new consortia setting was developed based on the average of two settings generated from RSM testing several combinations of consortia concentrations (5:1, 2:4, 3:3, 4:2, and 1:5). The combination of 5:1 Aspergillus niger B2484 and Trichoderma asperellum B1581 produced the most ethanol with 1.03 g/L, more than A. niger B2484, alone with 0.34 g/L of ethanol, indicating the potential of the combination of A. niger B2484 and T. asperellum B1581 co-culture for bioethanol production in CBP.